2014
DOI: 10.4103/2279-042x.132702
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems among medical ward patients in Jimma university specialized hospital, Southwest Ethiopia

Abstract: Objective:The increasing number of available drugs and drug users, as well as more complex drug regimens led to more side effects and drug interactions and complicates follow-up. The objective of this study was to assess drug-related problems (DRPs) and associated factors in hospitalized patients.Methods:A hospital-based cross-sectional study design was employed. The study was conducted in Jimma University Specialized Hospital, Jimma, located in the south west of Addis Ababa. All patients who were admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 12 publications
13
64
1
Order By: Relevance
“…From the literature review, Tigabu et al, has observed that the prevalence of DRPs in their study was found to be 73.5%. 17 Expecting similar results in our present study with 95% confidence interval (CI) and with 10% relative precision, the sample size was found to be 150 subjects. 150 patients satisfied the aforementioned criteria and enrolled for the study.…”
Section: Study Samplesupporting
confidence: 78%
“…From the literature review, Tigabu et al, has observed that the prevalence of DRPs in their study was found to be 73.5%. 17 Expecting similar results in our present study with 95% confidence interval (CI) and with 10% relative precision, the sample size was found to be 150 subjects. 150 patients satisfied the aforementioned criteria and enrolled for the study.…”
Section: Study Samplesupporting
confidence: 78%
“…It accounts for 62.4% of the total DTPs (236/378). It was also common in two other studies done at different hospitals of Ethiopia which were reported as 32.6% and 90.7% 14,15 . From these reports, it has been shown that there are variations in the prevalence among different settings.Such discrepancies might be explained in terms of availability of comprehensive treatment guidelines and professionals involved in the identification of DTPs particularly availability of clinical pharmacists in the clinical settings.…”
Section: Discussionmentioning
confidence: 68%
“…The average knowledge assessment score per person increased from 0.22 to 0.85 with the aid of patient counseling using PIL card (30 patients). This is by a study conducted by Varkey et al, (2007), which showed that the average number of discrepancies decreased from 5.24 to 2.46 per patient after patient counseling 17 .…”
Section: Fig 2: Percentage Of Intervention Acceptancementioning
confidence: 92%